Quality of life and associated clinical distress in fibromyalgia - G. Perpignano; L. Minerba; A. Denotti; C. Anedda; V. Ruggiero; E. Cacace (PAGEPress Publications, 2011)
Objectives: Fibromyalgia (FM) is a syndrome characterized by chronic, diffuse musculoskeletal pain and by a low pain threshold at specific anatomical points (tender points). Numerous other conditions (Irritable bowel syndrome, tension-type headache, migraine headaches, etc.) may overlap with FM. Aim of this study was to evaluate the quality of life and associated clinical distress in patients with FM. Methods: 53 females affected by primary fibromyalgia and 40 healthy females were examined were examined by an experienced rheumatologist and interviewed using the Fibromyalgia Impact Questionnaire (FIQ). Clinical monitoring included Visual Analogue Scale for pain and pain pressure threshold measurements. Results: Mean FIQ scores were 66.39±14.94 in FM patients and 13.15±5.37 in control subjects and the difference was statistically significant. Among associated clinical distress higher frequencies have been found for paraesthesia (87%), sleep disturbance (72%), tension type headache (70%), oto-vestibule syndrome (72%) and irritable colon (60%). An R.O.C. bend was developed in the presence of paraesthesias and oto-vestibule syndromes at the same time. This allowed us to identify a FIQ cut off value of 66.85 so FM patients were divided into 2 groups according to their FIQ scores: severe degree and mild or slight degree. Conclusions: Based on our data, it would appear possible to use a FIQ value equal to or higher than 66.85 for the clinical picture of FM to be classified as severe.